Optimized synthesis of aroyl-S,N-ketene acetals by omission of solubilizing alcohol cosolvents - Krenzer, Julius; Müller, Thomas J. J. (Beilstein Journal of Organic Chemistry, 2025)
Aroyl-S,N-ketene acetals are obtained by condensation of aroyl chlorides and 2-methyl-N-benzylbenzothiazolium salts in 1,4-dioxane at room temperature in short reaction time in 20–99% yield. This protocol represents a considerable improvement over the standard synthesis in 1,4-dioxane/ethanol mixtures at elevated temperatures.
Keywords: aroyl chlorides; aroyl-S,N-ketene acetals; condensation; Einhorn-type acylation; 2-methyl N-benzyl benzothiazolium salts